Anabaena/Dolichospermum as the source of lethal microcystin levels responsible for a large cattle toxicosis event. (January 2019) - Dreher, Theo W.; Collart, Lindsay P.; Mueller, Ryan S.; Halsey, Kimberly H.; Bildfell, Robert J.; Schreder, Peter; Sobhakumari, Arya; Ferry, Rodney
Abstract: Thirty-two 14-month old steers died during a period of four days (19–23 June 2017) after drinking from Junipers Reservoir (southeastern Oregon, USA) during a cyanobacterial bloom. Clinical and histopathological findings were consistent with acute liver disease, and microcystin-LR was present at 3000 μg/L in a reservoir water sample and at 7100 μg/L in the rumen contents of one of the mortalities. Serum biochemistry and histological examination indicated severe liver damage consistent with microcystin toxicosis. Microscopic observation of reservoir water samples, limited to frozen or poorly stored and partially degraded samples, indicated the presence of abundant Anabaena/Dolichospermum, but the presence of other toxic cyanobacteria such as Microcystis could not be excluded. Metagenomic analysis showed the presence in these samples of a single cyanobacterium whose cpcBA, rpoB and rbcL genes indicated membership in the Anabaena/Dolichospermum genus. The sequence of a complete mcy gene cluster with homology to previously identified Anabaena mcy genes was recovered. These results emphasize the capacity for Anabaena/Dolichospermum blooms to produce lethal levels of microcystin, posing a danger to public health and livestock. Further, our findings indicate that such occurrences can occur outside the far-northern latitudes in which microcystin-producing Anabaena have typically been found. Graphical abstract: Image 1 Highlights: Death of 32 cattle emphasizes the danger of livestock poisoning by cyanobacterial toxins. Deaths resulted from microcystin-LR toxicosis. The producing organism was genetically identified as a member of the Anabaena/Dolichospermum genus. Anabaena/Dolichospermum blooms can be as potent a source of microcystins as is common for Microcystis or Planktothrix .